Structural Model for Dihydropyridine Binding to L-type Calcium Channels - Tikhonov, Denis B. (American Society for Biochemistry and Molecular Biology, 2009)
1,4-Dihydropyridines (DHPs) constitute a major class of ligands for L-type Ca(2+) channels (LTCC). The DHPs have a boat-like, six-membered ring with an NH group at the stern, an aromatic moiety at the bow, and substituents at the port and starboard sides. Various DHPs exhibit antagonistic or agonistic activities, which were previously explained as stabilization or destabilization, respectively, of the closed activation gate by the portside substituents. Here we report a novel structural model in which agonist and antagonist activities are determined by different parts of the DHP molecule and have different mechanisms. In our model, which is based on Monte Carlo minimizations of DHP-LTCC complexes, the DHP moieties at the stern, bow, and starboard form H-bonds with side chains of the key DHP-sensing residues Tyr_IIIS6, Tyr_IVS6, and Gln_IIIS5, respectively. We propose that these H-bonds, which are common for agonists and antagonists, stabilize the LTCC conformation with the open activation gate. This explains why both agonists and antagonists increase probability of the long lasting channel openings and why even partial disruption of the contacts eliminates the agonistic action. In our model, the portside approaches the selectivity filter. Hydrophobic portside of antagonists may induce long lasting channel closings by destabilizing Ca(2+) binding to the selectivity filter glutamates. Agonists have either hydrophilic substituents or a hydrogen atom at their portside, and thus lack this destabilizing effect. The predicted orientation of the DHP core allows accommodation of long substituents in the domain interface or in the inner pore. Our model may be useful for developing novel clinically relevant LTCC blockers.